Impact of Postoperative Opioid Use on 2-Year Patient-Reported Outcomes in Knee Surgery Patients - Song, Xuyang; Sajak, Patrick M.J.; Aneizi, Ali; Alqazzaz, Aymen; Burt, Cameran I.; Ventimiglia, Dominic J.; Meredith, Sean J.; Leong, Natalie L.; Packer, Jonathan D.; Henn, R. Frank, III (The Journal of Knee Surgery, 2021)
The purposes of this study were to identify the patient characteristics associated with refilling a postoperative opioid prescription after knee surgery and to determine whether refilling opioids is associated with 2-year patient-reported outcomes. We hypothesized that postoperative refill of opioids would be associated with worse 2-year patient-reported outcomes. We studied 192 patients undergoing knee surgery at a single urban academic institution. Patients completed multiple patient-reported outcome measures preoperatively and 2 years postoperatively, including six Patient-Reported Outcomes Measurement Information System (PROMIS) domains, the International Knee Documentation Committee (IKDC) questionnaire, numeric pain scale scores for the operative knee and the rest of the body, Marx Activity Rating Scale, as well as measures of met expectations, improvement, and satisfaction. Total morphine equivalents (TMEs) were calculated from a regional prescription monitoring program. Patients who refilled a postoperative opioid prescription were compared with those who did not, and TMEs were calculated for those who refilled (Refill TMEs). One hundred twenty-nine patients (67%) refilled at least one postoperative opioid prescription. Black race, older age, higher average body mass index (BMI), smoking, greater medical comorbidities, preoperative opioid use, lower income, government insurance, and knee arthroplasty were associated with refilling opioids. Greater Refill TMEs was associated with black or white race, older age, higher average BMI, smoking, greater medical comorbidities, preoperative opioid use, government insurance, and unemployment. Refilling opioids and greater Refill TMEs were associated with worse postoperative scores on most patient-reported outcome measures 2 years after knee surgery. However, refilling opioids and greater Refill TMEs did not have a significant association with improvement after surgery. Multivariable analysis controlling for potential confounding variables confirmed that greater postoperative Refill TMEs independently predicted worse 2-year PROMIS Physical Function, 2-year PROMIS Pain Interference, and 2-year IKDC knee function scores. Postoperative refill of opioids was associated with worse 2-year patient-reported outcomes in a dose-dependent fashion. These findings reinforce the importance of counseling patients regarding opioid use and optimizing opioid-sparing pain management postoperatively.
Keywords: knee surgery; opioids; patient-reported outcomes; total morphine equivalent